Human tetherin exerts strong selection pressure on the HIV-1 group N Vpu protein - Sauter, Daniel; Fritz, Joëlle; Fackler, Oliver Till (PLoS pathogens, 2012)
HIV-1 groups M and N emerged within the last century following two independent cross-species transmissions of SIVcpz from chimpanzees to humans. In contrast to pandemic group M strains, HIV-1 group N viruses are exceedingly rare, with only about a dozen infections identified, all but one in individuals from Cameroon. Poor adaptation to the human host may be responsible for this limited spread of HIV-1 group N in the human population. Here, we analyzed the function of Vpu proteins from seven group N strains from Cameroon, the place where this zoonosis originally emerged. We found that these N-Vpus acquired four amino acid substitutions (E15A, V19A and IV25/26LL) in their transmembrane domain (TMD) that allow efficient interaction with human tetherin. However, despite these adaptive changes, most N-Vpus still antagonize human tetherin only poorly and fail to down-modulate CD4, the natural killer (NK) cell ligand NTB-A as well as the lipid-antigen presenting protein CD1d. These functional deficiencies were mapped to amino acid changes in the cytoplasmic domain that disrupt putative adaptor protein binding sites and an otherwise highly conserved ßTrCP-binding DSGxxS motif. As a consequence, N-Vpus exhibited aberrant intracellular localization and/or failed to recruit the ubiquitin-ligase complex to induce tetherin degradation. The only exception was the Vpu of a group N strain recently discovered in France, but originally acquired in Togo, which contained intact cytoplasmic motifs and counteracted tetherin as effectively as the Vpus of pandemic HIV-1 M strains. These results indicate that HIV-1 group N Vpu is under strong host-specific selection pressure and that the acquisition of effective tetherin antagonism may lead to the emergence of viral variants with increased transmission fitness., Differences in their degree of adaptation to humans may explain why only one of four ape-derived SIV zoonoses spawned the AIDS pandemic. Specifically, only HIV-1 strains of the pandemic M group evolved a fully functional Vpu that efficiently antagonizes human tetherin and degrades CD4. In comparison, the rare group N viruses gained some anti-tetherin activity but lost the CD4 degradation function. Here, we show that the N-Vpu transmembrane domain has adapted to interact with human tetherin and identified the mutations that enable this interaction. However, we also show that most N-Vpus remain poor tetherin antagonists and fail to reduce the surface expression of CD4, the natural killer cell ligand NTB-A and the lipid-antigen presenting protein CD1d. This is due to mutations in their cytoplasmic region that are associated with aberrant protein localization and impaired interaction with the ubiquitin/proteasome pathway. A remarkable exception is the Vpu of the first HIV-1 N strain known to be transmitted outside of Cameroon, which contains a functional cytoplasmic domain and is a highly effective tetherin antagonist. These data indicate that group N viruses are still adapting to humans and that the acquisition of potent anti-tetherin activity may eventually lead to the emergence of viral variants that exhibit increased transmission fitness.
Gesehen am 18.09.2018